The role of civil liability in ensuring police responsibility for failures to act after Michael and DSD - Hyde, Richard (EJoCLI, 2016)
Police failures may contribute to a failure to prevent injury, or worse. The question of whether the police should be liable for such investigatory failures has exercised the higher courts frequently since the seminal case of Hill. The Supreme Court has recently revisited the question in the case of Michael, holding that the police will not be liable for a failure to prevent injury unless there are special circumstances showing an assumption of responsibility. In parallel to the developments in negligence, claims have been brought under the Human Rights Act, with an argument that the failures by the police led to injury or death, breaching obligations under the European Convention on Human Rights. Such a claim was successful before the Court of Appeal in DSD.This article seeks to analyse these two parallel trends, and to consider whether civil liability after Michael and DSD provides an avenue for obtaining both compensation and accountability.